2020
DOI: 10.1111/idj.12539
|View full text |Cite
|
Sign up to set email alerts
|

Need for dental care drives utilisation of dental services among children in Saudi Arabia

Abstract: Objectives: This study used Andersen's predisposing, enabling and need behavioural model to predict factors that influence utilisation of oral health services for children in Saudi Arabia. Methods: The model was tested in a random sample of parents of third-and eighth-grade children in Jeddah (n = 1,668) using the access to care questionnaire adapted from the Basic Screening Survey. Predisposing (sex, parent education, nationality); enabling (school type, family income, government financial support, health ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 17 publications
5
53
0
Order By: Relevance
“…The process of study selection is shown in Figure 1 (flow chart [21]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [22][23][24][25][26][27][28][29][30][31] and 31 studies investigating adults ). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The process of study selection is shown in Figure 1 (flow chart [21]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [22][23][24][25][26][27][28][29][30][31] and 31 studies investigating adults ). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
“…Four [23,25,27,31] out of the six studies which examined age found a positive association with dental service use, whereas two studies did not identify such a link [29,30]. While two studies [22,26] found a link between being female and increased dental service use, five studies did not find a significant association between gender and dental service use [23,[28][29][30][31]. Other predisposing characteristics were only examined in a few studies.…”
Section: Predisposing Characteristicsmentioning
confidence: 95%
See 3 more Smart Citations